A comparison of the effectiveness of embroidery thread and unwaxed dental floss in dental plaque removal - Canlas, Maritess C.; Cham, Winston (Adviser).
Flossing is necessary in order to remove dental plaque in areas not accessible to toothbrushing. However, flossing is not readily accepted due to its high cost. The general objective of this study is to compare the effectiveness of embroidery thread (the experimental flossing material) and unwaxed dental floss (the control flossing material) in their ability to remove dental plaque. It is the hope of this study to come up with an alternative flossing material that is cheaper and yet still as effective as the regular dental floss. Fifteen senior students of Pampanga High School who have complete set of teeth, who have undergone dental prophylaxis at least 6 months ago, and who are not wearing fixed orthodontic appliances were chosen as subjects using a questionnaire. Questionnaires were distributed for the selection of subjects in order to disregard some variables such as absence or presence of all reference teeth, and absence or presence of plaque retention factors such as calcular deposits and fixed orthodontic appliances. The method of data collection included: staining of plaque with disclosing tablet, recording of sites positive with plaque, flossing, re-staining, and recording of positive sites left after flossing. Clinical observation and statistical analysis using the paired t-test at 95% confidence limit showed that embroidery thread is not as effective as unwaxed dental floss in its ability to remove dental plaque.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental plaque; Dental floss